The Importance of Using SWOT Analysis in Business Success - Belal Dahiam Saif Ghaleb (International Journal of Asian Business and Management, 2024)
The SWOT analysis is a strategic planning tool that helps businesses identify their strengths, weaknesses, opportunities, and threats. This article explores the importance of SWOT analysis in achieving business success. Through a comprehensive literature review, it examines the role of SWOT analysis in strategic planning, decision-making, and organizational growth. The methodology includes a review of case studies and empirical data from various industries. The findings highlight how SWOT analysis aids in aligning strategies with market dynamics and enhancing competitive advantage. The discussion delves into the practical implications and limitations of SWOT analysis, concluding with recommendations for its effective use in business strategy formulation